Numbers, Predictions & War : Using History to Evaluate Combat Factors and Predict the Outcome of Battles - Dupuy, T. N. Colonel (London Macdonald and Jane's, 1979)
This remarkable book for war-gamers, political and military analysts, and anyone else interested in military history - or in future history - is the result of a series of studies undertaken for the United States Department of Defense and for the British Defence Operational Analysis Establishment. In order to prepare for strategic contingencies, military planners wanted to know what modern historical experiences could tell them about teh nature of combat and the reasons for a group's success or failure. Some Pentagon officials also needed to find out the extent to which these historical experiences could provide a basis for predicting battle outcomes.
Include Graph, Epilogue, Inex and Appendix.
Keywords: Military Art and Science--Mathematical Models -- War Games